The relationship between family firms ownership and control with discretionary accruals / Nor Hannan Mohd Zin - Mohd Zin, Nor Hannan (2013)
The primary objective of this study is to investigate whether there is relationship between family ownership and controls with discretionary accruals in Malaysia. This study employed a sample of 478 listed firm's observation of Malaysian listed companies in the period of year 2012. The samples consist of 275 family firms and 203 non family firms. First, the study examines the association between discretionary accruals with family ownership. The result suggest that discretionary accruals has association with the family ownership which indicates that high percentage of the firm's share hold by families will result in low accounting discretion being reported (Machunga and Teitel, 2009). Second, this study examines the association between discretionary accruals with family controls. Surprisingly, the result suggests that discretionary accrual has association with the family controls. This indicates that high percentage of family members being appointed and holds position in the board result in high accounting discretion. This study also found that firm size, leverage, board size, directors independence, return on equity, CEO duality, BIG 4 auditors and industry influence discretionary accruals occurrence in family firms specifically in Malaysian environment.